2005
DOI: 10.1016/j.ccr.2005.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock phenocopies E1B-55K late functions and selectively sensitizes refractory tumor cells to ONYX-015 oncolytic viral therapy

Abstract: ONYX-015 is an E1B-55K-deleted adenovirus that has promising clinical activity as a cancer therapy. However, many tumor cells fail to support ONYX-015 oncolytic replication. E1B-55K functions include p53 degradation, RNA export, and host protein shutoff. Here, we show that resistant tumor cell lines fail to provide the RNA export functions of E1B-55K necessary for ONYX-015 replication; viral 100K mRNA export is necessary for host protein shutoff. However, heat shock rescues late viral RNA export and renders re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 59 publications
1
88
0
Order By: Relevance
“…7 The therapeutic index of oncolytic adenovirus could also be increased by fever and the concomitant induction of a heat shock response could significantly improve ONYX-015 cancer therapy. 26,27 In the current trial of H103, an association between fever and clinical benefit was not found. Mild-to-moderate hematological toxicities have generally been observed in the trials of adenoviruses using the virus as a gene therapy vector or oncolytic virus.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…7 The therapeutic index of oncolytic adenovirus could also be increased by fever and the concomitant induction of a heat shock response could significantly improve ONYX-015 cancer therapy. 26,27 In the current trial of H103, an association between fever and clinical benefit was not found. Mild-to-moderate hematological toxicities have generally been observed in the trials of adenoviruses using the virus as a gene therapy vector or oncolytic virus.…”
Section: Discussionmentioning
confidence: 58%
“…Although HSPs may have potential protective roles in cancer as molecular chaperones toward proteins damaged by extreme environmental stress, 20 as capacitors of phenotypic mutations due to the cancer cell's genetic instability 21 or as multiple pathway transductors in self-sufficient survival signaling, 22 HSPs may also play assistant functions to oncolytic virus by greatly enhancing oncolytic virus's efficacy on the other hand. 23 In the competition between cancer cells and oncolytic viruses, we prefer the assumption that HSPs may be more helpful to oncolytic virus compared with cancer cells, because HSP-armed oncolytic adenovirus experienced more cytotoxicity to tumor cells than the oncolytic virus without HSP gene in our earlier study. 19 In addition, given the transient expression of transgenes delivered by adenovirus, which seldom integrates into the cell's genome, 24 HSP expression induced by H103 will be abolished after the clearance of the virus from cancer cells and may have no long-lasting effect on the survival of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…33 Heat shock response rescues late viral RNA export and renders refractory tumor cells permissive to dl1520. 53 A specific question that we investigated in this study is how dl1520 can efficiently replicate in some cancer cells, but its replication is limited in other cancer cells. In order to study this question in a cellular environment that excludes effect of p53 factor, we used p53-null Hep3B and Saos2 cells as models.…”
Section: Adenoviruses-induced Cell Cycle Changes In Hep3b and Saos2 Cmentioning
confidence: 99%
“…Detailed analysis demonstrated that the loss of the mRNA transport function provided by E1b-55k could be complimented in tumor cell lines, suggesting a novel mechanism of tumor-selective viral replication. 8 However, complementation of lost functions due to the deletion of E1b-55k was incomplete in most tumor cells. Consequently, the titer and cytolytic activity of dl1520 in tumor cells was often one to two logs lower than wild-type Ad5 in the same tumor cells.…”
Section: Introductionmentioning
confidence: 99%